Symptoms experiences and attitudes towards menstruation among adolescent girls - Öztürk, Ruşen; Güneri, Sezer Er (Journal of obstetrics and gynaecology, 2021)
The study aimed to analyse the factors affecting menstrual symptoms and attitudes among adolescent girls and the relationship between them. The sample of the cross-sectional, descriptive and analytical research was composed of 604 adolescent girls studying at a university. Individual Information Form, Menstruation Symptom Questionnaire (MSQ) and Menstrual Attitude Questionnaire (MAQ) were used as data collection tool in the research. Average age of the students was 21.22 ± 1.71, and average menstrual cycle length was 29.3 ± 7.85 days. MSQ mean score was 69.84 ± 15.48 and MAQ mean score was 103.10 ± 9.84. These results are important for showing that students perceive menstruation as a natural phenomenon, despite significant menstrual symptoms.Impact statement The intensity of menstrual symptoms is associated with negative menstrual attitudes. But, there have been few studies on the relationship between menstruation symptoms and attitudes and their impact on menstrual problems in Turkish adolescents. Adolescents' menstrual complaints are common, but their attitudes towards menstruation are positive. The lack of a significant relationship between menstrual symptoms and attitudes were more likely to be explained by the fact that young girls perceive menstruation as a natural phenomenon even though they have so many symptoms. Further study should be extended to various cultures and destinations to understand the effect of culture on menstruation that rural areas may be surrounded by taboos and myths which might affect the negative attitude.